Wykorzystanie map cech Kohonena we wstępnej analizie danych - Tarczyński, Grzegorz (The Use of Kohonen's Self Organizing Maps in Exploratory Data Analysis, 2007)
This paper describes some differences between Exploratory Data Analysis and Statistical Data Analysis. The advanced projection technics of Kohonen's Self Organizing Maps is used for measuring the life quality in Polish districts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 255-265